PEMBERDAYAAN MASYARAKAT KELURAHAN MERJOSARI, KECAMATAN LOWOKWARU, MALANG MELALUI PENINGKATAN KETRAMPILAN PENGOLAHAN PASCA PANEN - Dwi Susilowati (Universitas Negeri Medan, 2022)
The majority of the products produced by the residents' yards in RW 11 Merjosari, Lowokwaru Subdistrict, Malang City are horticulture and catfish commodities. Because the qualities of horticulture and catfish are easily damaged, post-harvest processing innovation is required. However, the community lacks expertise in good and correct post-harvest processing. The activity's goal is to increase abilities in post-harvest processing technology of horticulture commodities into juice and catfish processing into abon using a good and proper technique. The activities were carried out in the village of Merjosari, Lowokwaru District, Malang City, by the peasant organisation